IMPACT OF LEADERSHIP STYLE (TRANSFORMATIONAL AND TRANSACTIONAL) ON PT BUMA SITE LATI'S SAFETY PERFORMANCE (The Indonesian Journal of Business Administration, 2021)
PT BUMA LMO as a coal mining service company located in the operational area of PT Berau Coal has the largest production capacity and has a high potential for accidents. Increased production that is not balanced with a safety culture and safety commitment from management has an impact on safety performance in the company. A leadership culture in safety is very influential in creating a safety pattern in a company. Leadership in the organization at PT BUMA LMO is very much needed in safety management to create a conducive safety culture. The SR and FR data shows that there has been a significant increase of accidents that occurred at PT BUMA LMO during 2013-2019. This is an important consideration to improve the safety performance of PT BUMA LMO because the safety performance factor is a prerequisite for contractors who meet the requirements, and become a determining factor for production volume. In this study, research on leadership styles (transformational and transactional) in PT BUMA LMO is a factor to be examined.Keywords: Leadership, Transactional Leadership, Transformational Leadership, Safety Performance